2019
DOI: 10.48550/arxiv.1904.11600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scrutinizing Various Phenomenological Interactions In The Context Of Holographic Ricci Dark Energy Models

Ehsan Sadri,
Martiros Khurshudyan,
Ding-fang Zeng

Abstract: In this paper, we examine two types of interacting holographic dark energy model using Pantheon supernova data, BAO BOSS DR12, CMB Planck 2015, fgas (gas mass fraction) and SZ/Xray (Sunyaev-Zeldovich effect and X-ray emission) data from galaxy clusters (GC). In particular, we considered the Holographic Ricci dark energy and Extended holographic Ricci dark energy models. During this analysis we considered seven type of phenomenological interaction terms (three linear and four non-linear)

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…In our recent work, we compared different phenomenological linear and non-linear interaction cases in the framework of the holographic Ricci dark energy model [46] and we found that the linear interaction Q = 3Hbρ D and Q = 3Hbρ m are the best cases among the others. Accordingly, in this work we take Q = 3Hbρ m in our calculations.…”
Section: The Hubble Horizonmentioning
confidence: 99%
“…In our recent work, we compared different phenomenological linear and non-linear interaction cases in the framework of the holographic Ricci dark energy model [46] and we found that the linear interaction Q = 3Hbρ D and Q = 3Hbρ m are the best cases among the others. Accordingly, in this work we take Q = 3Hbρ m in our calculations.…”
Section: The Hubble Horizonmentioning
confidence: 99%
“…In fact, there are different choices for Q term in order to study the dynamics of interacting DE models. In the recent work, the different phenomenological linear and non-linear interaction cases in the framework of the holographic Ricci dark energy model have been investigated and the results show that the linear interaction Q = 3Hbρ D is the best case among the others [65]. Accordingly, in the herein model, we take Q = 3Hb 2 ρ D as the interaction term, in which b 2 is a coupling constant.…”
Section: Fractal Cosmologymentioning
confidence: 99%
“…Here γ and c dimensionless constants and deceleration parameter is defined in equation (5). Recently, Sadri et al [114] have compared different phenomenological linear as well as non-linear interaction cases in the framework of the holographic Ricci DE model and they found that the linear interaction are the best cases among the others. Inspired by the works of Pavon and Zimdahl [115], Sadeghi et al [116], Honarvaryan et al [117], Zadeh et al [82] and Sadri [84], in this work, we consider the linear interacting term as Q = 3c 2 H(ρ m + ρ de ).…”
Section: Interacting Modelmentioning
confidence: 99%